Introduction. - Mitchell, Katharine; Ramsey-Portolano, Catherine (Italianist)
An introduction is presented in which the editor discusses several reports published within issue on topics including writings of Anna Radius Zuccari known as Neera; Neera's ideological beliefs; and fundamental admiration of Neera's writings.